2016
DOI: 10.1155/2016/2981639
|View full text |Cite
|
Sign up to set email alerts
|

A Glyoxalase-1 Knockdown Does Not Have Major Short Term Effects on Energy Expenditure and Atherosclerosis in Mice

Abstract: Objective. Glyoxalase-1 is an enzyme detoxifying methylglyoxal (MG). MG is a potent precursor of advanced glycation endproducts which are regarded to be a key player in micro- and macrovascular damage. Yet, the role of Glo1 in atherosclerosis remains unclear. In this study, the effect of Glo1 on mouse metabolism and atherosclerosis is evaluated. Methods. Glo1 knockdown mice were fed a high fat or a standard diet for 10 weeks. Body weight and composition were investigated by Echo MRI. The PhenoMaster system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The loss of AKR1b3 in apoE-knock-out mice not only increased AGE accumulation but also the formation of atherosclerotic lesions. However, Glo1 knock-down mice on the apoE background did not show any differences in either MG-derived AGEs or enhanced formation of atherosclerosis [49]. These studies would suggest that the loss of Glo1 alone is insufficient to trigger the development of complications in diabetes.…”
Section: Discussionmentioning
confidence: 81%
“…The loss of AKR1b3 in apoE-knock-out mice not only increased AGE accumulation but also the formation of atherosclerotic lesions. However, Glo1 knock-down mice on the apoE background did not show any differences in either MG-derived AGEs or enhanced formation of atherosclerosis [49]. These studies would suggest that the loss of Glo1 alone is insufficient to trigger the development of complications in diabetes.…”
Section: Discussionmentioning
confidence: 81%
“…Glo1-knockout mice showed reduced anxiety-like, but increased depression-like behavior [49]. Interestingly, there were no changes in body fat composition, body weight, plasma glucose levels as well as plasma triglycerides and cholesterol concentrations compared to wildtype littermates [50]. This applied for both, mice fed a standard or high fat diet.…”
Section: Systemic Effects Of Mg and Ages In Rodentsmentioning
confidence: 83%
“…Critically, in that study, levels of vascular AGEs were not reduced by overexpression of GLO1. Others showed similar findings in atherosclerosis and demonstrated that in Glo1 -knockdown mice, methylglyoxal-derived AGE levels were not increased and atherosclerosis did not differ when compared to wild-type animals [38]. Hence, the specific AGEs biologically active in diabetes and atherosclerosis may not all be modulated through the actions of GLO1.…”
Section: Glycation and Atherosclerosis: Updatesmentioning
confidence: 85%
“…CD36 was shown to mediate uptake and degradation of AGEs by adipocytes [63] and through CD36 actions, leptin is downregulated in these cells [64, 65]. Intriguingly, in vivo studies in GLO1 knockdown mice fed high fat diet did not reveal altered body mass, composition or energy expenditure versus the wild-type controls [38]. Such findings, analogous to those in atherosclerosis considered above, suggest that perhaps non-GLO1-dependent AGEs also contribute importantly to obesity and energy balance.…”
Section: Glycation and Obesity: Emerging Linksmentioning
confidence: 99%